TWO-FREQUENCY CROSS-SLOT ANTENNA WITH RESONANT COLD ELECTRON BOLOMETERS FOR APPLICATION IN CORE SPACE MISSION - L. S. Kuzmin; A. V. Chiginev (Приборы и методы измерений, 2017)
Measurements of the CMB properties is an actual problem of modern astronomy. The aim of the present paper is the numerical modeling of the two-frequency planar cross-slot antenna designed for operation in the receiving system of the orbital telescope Cosmic Origins Explorer (COrE), developed by the European Space Agency to measure the CMB.The proposed antenna is a planar metal layer on the dielectric substrate, and comprising a set of four slots intersecting each other at right angles. The composition also includes a set of microstrip lines for transmitting a signal from the resonant slots to cold-electron bolometers, and a lens for forming the main beam of the radiation diagram. Calculation of the antenna system is made by electrodynamic modeling software package CST Microwave Studio. As a result of the modeling, the radiation diagram of the antenna in two frequency channels as well as its frequency characteristics are obtained.The calculation gives the following characteristics of the receiving system on the basis of cross-slot antenna: width of the main beam of the radiation diagram – 24.3° and 19.5°, the ellipticity of the beam – 4.2 % and 0.3 %, the bandwidth – 14.9 GHz and 19.0 GHz, polarization resolution – 23.4 dB and 29.6 dB, where the former value refers to the 75 GHz channel, and the latter refers to 105 GHz channel.It is proposed to use a cross-slot antenna in dual-frequency mode together with resonant cold-electron bolometers to work in the receiving system of the orbital telescope COrE. Comparison of the calculated antenna characteristics with the requirements set by the European Space Agency, have shown the possibility of using this type of antenna as part COrE mission.